The involvement of actin, calcium channels and exocytosis proteins in somato-dendritic oxytocin and vasopressin release - Tobin, Vicky A.; Leng, Gareth; Ludwig, Mike (Frontiers in Physiology, 2012)
Hypothalamic magnocellular neurons release vasopressin and oxytocin not only from their axon terminals into the blood, but also from their somata and dendrites into the extracellular space of the brain, and this can be regulated independently. Differential release of neurotransmitters from different compartments of a single neuron requires subtle regulatory mechanisms. Somato-dendritic, but not axon terminal release can be modulated by changes in intracellular calcium concentration ([Ca2+]) by release of calcium from intracellular stores, resulting in priming of dendritic pools for activity-dependent release. This review focuses on our current understanding of the mechanisms of priming and the roles of actin remodelling, voltage-operated calcium channels and SNARE proteins in the regulation somato-dendritic and axon terminal peptide release.